Innovative government initiatives to prevent upper secondary school dropout: organisational learning and institutional change at the local level. Issue 1 (2017) - Homme, Anne; Hope, Kristin Lofthus
This paper investigates how a specific public innovation in Norway, the New Possibilities Strategy, has influenced the implementation of anti-dropout measures at local education authority levels. In Norway, approximately 100% of all 16-year-olds start upper secondary education. However, about one-third of the students does not complete or graduate within a five-year period. Dropout rates have received increasing political attention as a societal problem, resulting in a number of different policy strategies. The paper aims to reduce the lack of knowledge on how innovations in education may contribute to solving an apparently stable educational problem, by enhancing learning outcomes and reducing the number of young people that do not complete and graduate from upper secondary education. Utilising a framework for government and public sector innovation and implementation, together with concepts of institutional change, will give a new understanding of how a public innovative strategy influences organisational learning.